Caracterização parcial do extrato etanólico de Cymbopogon citratus e capacidade de indução de mecanismo de resistência em soja - Temporal, Walter Magri (2014)
Compounds produced by medicinal plants with capacity to activate defense mechanisms of plants have been studied as an ecologically viable tool in agriculture. Among these plants islemongrass (Cymbopogon citratus). This study aimed to assess biochemical aspects of soybean when treated with ethanolic extracts of C. citratus, obtained from material collected in summer and winter. The ability to gliceolin induction and pathogenesis-related proteins (PR - proteins) was assessed, as the antimicrobial action against Colletotrichum truncatum and Corynespora cassiicola. Cotyledons of soybean and soybean leaves were treated with plant extracts, as well as acibenzolar -S- methyl (ASM) (100 mg a.i. L-1) and distilled water. Soybean plants treated samples were withdrawn at 0, 12, 24, 48 and 72 hours after treatments application for enzymatic analysis. Were determined: gliceolin induction, and changes in the peroxidase activity, polyphenol oxidase, phenylalanine ammonialyase, β-1,3-glucanase and chitinase. The mycelial growth assessments were performed for 120 hours. The parameter evaluated was the inhibition of colony growth compared with water standard. In general, fungi showed differential responses to each other. The highest concentration of the extract negatively affected C. truncatum, while C. cassiicola used nutrients present in the medium for its growth. Biochemical analyzes revealed that, compared to the peroxidase activity in soybean cotyledons, there was decrease in enzyme activity when compared to standards, with the exception of treatments originated from material collected in the summer. In leaves, the peroxidase activity was increased by all treatments. The β-1, 3-glucanase activity in cotyledons was mostly increased by summer extract at 200 and 400 mg. L-1. In leaves, the β-1,3-glucanases activity was increased by all treatments, with no effect of concentration. There was increased activity of polyphenol only using the winter extract. There was no significant difference for FAL in soybean cotyledons as well as in leaf samples. Lower ratings to the negative standard suggested that extracts could contain inhibitors of this enzyme. The enzymatic activity of chitinase in soybean cotyledons was increased only with the use of extract of winter material. For all enzymes, increased activity was observed mainly after 24 hours of treatment application. This period of time is required for metabolites redirection to defense. Chromatographies allowed to obtain fractions with effect on cotyledons. In ion exchange chromatography, fractionation efficiency was observed only with glyceollin elicitors, β-1,3-glucanases and FAL, while for exclusion chromatography was not possible to separate elicitors. Defense mechanisms activated in soybean by the application extracts of lemon grass were noted, and may vary when plant material is harvested in different seasons. The findings may enable the development of alternative methods to control plant diseases.